Percepción sobre los servicios ecosistémicos del lago Moronacocha con el bienestar socioambiental de las familias aledañas, en Iquitos. Loreto. 2021 - Mamani del Castillo, Angie Estrella (2022)
The purpose of the study was to understand the perception of ecosystem services and their impact on the socio-environmental well-being of the riverside families of Lake Moronacocha. Descriptive, cross-sectional level research. The survey was transmitted as a data collection instrument with a non-probabilistic sample n (50). Between 30 and 40% of the families show regular to good levels in cognitive, affective and behavioral aspects, with disagreement regarding basic services provided by the government, with greater interest in improving the health of the lake, the families identify with the landscape and adopt to maintain attractiveness, between 38 and 24% of families show a medium to good level of well-being in terms of governance, peri-urban space in relation to coexistence in satisfaction of their needs for ecosystem services in the cultural, provision , regulation and support; the lake will favorably affect the well-being of riverside families as long as it is preserved, now it is not reflected in a high level of well-being for most of the riverside people, the study has partially prevented us from understanding the biophysical conditions of the lake, how families feel about their use, as well as glimpse what social, environmental, and economic aspects should be included in an ecosystem development program; we deduce that the lake, insofar as it is better preserved, will favorably affect the well-being of the riverside families; in the present the incidence in the families is not reflected in a high well-being for the majority of the riverside residents.